Enhancing fund mobilization at Lien Viet Post Bank – Ninh Binh Province Branch - Tran, Quynh Hoa (Khoa Quốc tế, ĐHQGHN, 2020)
Based on actual requirements, theoretical basis, documents and research on the development of commercial banking in general and the development of capital mobilization at commercial banks in particular, I have chosen thesis for my thesis: “Enhancing fund mobilization at Lien Viet Post Bank – Ninh Binh Province Branch”. In this thesis, I use secondary sources from reports of Lien Viet Post Bank – Ninh Binh Province Branchto analyze and compare the development ofLien Viet Post Bank services and those of other local banks.